Pulmonary root translocation and Senning procedure for congenitally corrected transposition of great arteries with pulmonary stenosis: a case report - Bansal, Nikhil (Indian J Thorac Cardiovasc Surg, 2020)
Congenitally corrected transposition of the great arteries (CCTGAs) is a condition, which includes atrioventricular and ventriculoarterial discordant connections along with ventricular septal defect (VSD), pulmonary stenosis (PS), or pulmonary atresia (PA). Without treatment, progressive systemic ventricular failure begins, which is followed by sudden cardiac death by the fourth or fifth decade. We report a case of a 4-year-old with CCTGA, VSD, and PS operated by Senning procedure and pulmonary root translocation (PRT) with uneventful postoperative recovery. PRT overcomes problems with the right ventricle to the pulmonary artery conduit and maintains pulmonary valve function and growth capacity. Our initial experience with PRT in CCTGA indicates that it is a feasible surgical alternative for such patients.